Application of medium plasma associated electrolyte and ferrocene negative electrode in potassium ion half-cell
By designing electrolyte with medium plasma association degree and untreated commercial ferrocene materials, the problems of low capacity and poor cycle stability caused by volume changes in electrode materials in potassium ion batteries are solved, and efficient potassium storage performance and rapid reaction kinetics are achieved.
Patent Information
- Application Number
- CN202510220129.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-26
- Publication Date
- 2025-04-11
AI Technical Summary
The volume of the inorganic electrode material in potassium ion batteries varies greatly during the cycle, resulting in low battery capacity and poor cycle stability. It is difficult for commercial ferrocene (Fc) molecules to be directly used to construct highly efficient potassium storage negative electrode materials.
An electrolyte with medium plasma association degree (MIAE) was designed to optimize the ion association characteristics of the electrolyte by regulating the solvent molecular structure and salt concentration, and combining untreated commercial ferrocene materials to form a potassium ion half-cell with high compatibility and high performance.
The cycle life, potassium storage performance and reaction kinetics of the Fc negative electrode are significantly improved, forming stable interfacial chemistry, promoting rapid reaction kinetics and efficient potassium storage performance.
Smart Images

Figure CN119812441A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic electrolyte and metallocene electrode materials, and in particular relates to the application of a medium ion association electrolyte and a ferrocene (Fc) negative electrode material in a potassium ion half-cell. Background Art
[0002] Renewable electrode materials to build secondary energy storage batteries are an effective solution to meet the growing demand for energy devices and large-scale energy storage systems. PIBs are strong candidates for lithium-ion batteries due to the easy availability of potassium resources, low production costs, and the similarity of the charging / discharging mechanism of potassium-ion batteries to commercial lithium-ion batteries. The progress of potassium ion battery research is still seriously hindered by the large size and difficulty in embedding electrode materials in traditional battery systems. In particular, inorganic electrode materials undergo drastic volume changes during the cycle, resulting in problems such as low battery capacity and poor cycle stability. Organic active materials with adjustable molecular structures and soft lattice properties provide a new direction for improving the above problems. In addition, organic materials have other commendable features, including their greenness, low cost, and flexible synthesis methods, which are prerequisites for the development of potassium ion batteries with high energy density and cost-effectiveness.
[0003] To date, new organic molecules with multiple redox active sites (such as C=O, C=N, N=N and phenyl) and their corresponding modifications have been explored in a large number of research works. Fc is a "sandwich"-shaped organometallic compound containing an iron cation flanked by cyclopentadienyl anions, which has excellent electrochemical responsiveness, thermal stability and chemical resistance. The Fc-based metal organic framework has a unique structure that can reduce the solubility problem of Fc in organic electrolytes, thereby constructing a highly stable potassium storage anode material. In addition, Fc can also be used as an additive to inhibit the intermolecular agglomeration effect, thereby improving the cycle reversibility and storage performance of the conversion-type anode material. Although the potassium storage stability has been improved through molecular design based on Fc organic materials, how to directly use cost-effective and easily available commercial Fc molecules remains a difficult problem.
[0004] In general, side reactions ultimately depend on the composition of metal salts and organic solvents in the electrolyte, especially the relative content and interaction of their free and solvated states in the dissolved structure. High-concentration electrolytes with less free solvents and anion-rich solvated structures are developed for organic active materials to improve the cycle stability by inhibiting the dissolution of organic active materials and forming a high-quality solid electrolyte interface (SEI). However, traditional high-concentration electrolytes usually lead to a decrease in ionic conductivity and an increase in dynamic viscosity due to cation-anion interactions, which inevitably sacrifices the potassium storage kinetics.
[0005] This patent proposes a medium ion association electrolyte (MIAE) for Fc organic potassium storage anode. In order to solve the problems of active material dissolution, interface instability and slow reaction kinetics, we rationally control the molecular structure and salt concentration of the solvent and design a series of electrolytes with different ion association characteristics. The optimized MIAE based on ethylene carbonate (EC) exhibits high ionic conductivity, anion-rich solvation structure and high compatibility with Fc anode, providing a solid guarantee for stable interface chemistry and fast reaction kinetics. Summary of the invention
[0006] The present invention aims to provide an application of a medium ion association electrolyte and an Fc negative electrode material in a potassium ion half-cell
[0007] The technical solution to achieve the purpose of the present invention is:
[0008] The invention discloses an application of an electrolyte with a medium ion association degree and an Fc negative electrode material in a potassium ion half-cell, wherein the potassium ion half-cell comprises an organic electrolyte, Fc and potassium metal; the organic electrolyte is prepared by an ion association strategy to obtain a potassium bis(fluorosulfonyl)imide (KFSI)-based electrolyte with different ion association degrees; and the negative electrode material is a commercial ferrocene material that has not been treated in any way.
[0009] The application of the medium ion association electrolyte and Fc negative electrode material in the potassium ion half-cell uses three solvents with different properties: mixed ester-based solvents ethylene carbonate + dimethyl carbonate (EC + DMC) (volume ratio 1:1), propylene carbonate + dimethyl carbonate (PC + DMC) (volume ratio 1:1), and vinylene carbonate + dimethyl carbonate (VC + DMC) (volume ratio 1:1).
[0010] The application of the medium ion association electrolyte and Fc negative electrode material in potassium ion half-cell, the preparation of the electrolyte: in a glove box filled with argon (water and oxygen content <0.01ppm), a certain amount of KFSI is added to three solvents EC+DMC, PC+DMC, and VC+DMC respectively, and the mixture is stirred evenly to obtain a potassium ion battery electrolyte with a concentration of 1-5mol / L(M).
[0011] The medium ion association electrolyte and Fc negative electrode material are used in a potassium ion half-cell, and the mixing and stirring temperature is 30° C. and the time is 12 hours.
[0012] Compared with the prior art, the present invention has the following beneficial effects:
[0013] The invention adopts an ion association strategy when preparing an organic electrolyte, and designs a MIAE with high ion conductivity and rich anion solvation structure.
[0014] Since Fc is easily soluble in organic electrolytes and the poor compatibility between the two will lead to a decrease in potassium storage performance, it is necessary to design a matching electrolyte; the electrolyte of the present invention contains a metal salt and an organic solvent, three mixed ester-based solvents with different characteristics are EC+DMC, PC+DMC, VC+DMC, the metal salt is KFSI, the metal salt concentrations are 1, 3 and 5M, and the optimized electrolyte is 3M KFSI / EC+DMC.
[0015] The present invention effectively enhances the cycle life, potassium storage performance and reaction kinetics of the Fc negative electrode through the ion association strategy. The anion-rich solvation structure is formed in the optimized electrolyte, which promotes the formation of a stable SEI and reduces the dissolution of the Fc organometallic compound. In addition, the fast ion transport kinetics provides multiple guarantees for the Fc negative electrode material to achieve fast and stable potassium storage performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 Infrared spectra of electrolytes after adjusting the ion association characteristics and energy values calculated based on the corresponding peak shifts
[0017] Figure 2 Regulating the Raman spectrum of the electrolyte and obtaining the solvation structure ratio and solvent coordination number after fitting
[0018] Figure 3 Test on the solubility performance of ferrocene in regulating electrolyte
[0019] Figure 4 Comparison of potassium storage performance of ferrocene anode materials in electrolytes with different ion association degrees
[0020] Figure 5 Comparison of rate performance and performance of ferrocene anode materials at high current density in electrolytes with different ion association degrees
[0021] Figure 6 Comparison of potassium storage kinetics of ferrocene anode materials in different ion-association electrolytes
[0022] Figure 7 Study on the dependence of ferrocene anode materials on electrolyte solvents
[0023] Figure 8 Comparison of rate performance of ferrocene anode materials in electrolyte solvent-derived electrolytes
[0024] Fig. 9 Compatibility test of potassium in optimized EC-based medium plasma association electrolyte DETAILED DESCRIPTION
[0025] The present invention is further described below in conjunction with specific embodiments.
[0026] Example 1
[0027] The invention discloses an application of an electrolyte with a medium ion association degree and an Fc negative electrode material in a potassium ion half-cell. The potassium ion half-cell comprises an organic electrolyte, Fc and potassium metal. The organic electrolyte is prepared by an ion association strategy to obtain a potassium bis(fluorosulfonyl)imide (KFSI)-based electrolyte with different ion association degrees. The negative electrode material is a commercial ferrocene material that has not been treated in any way.
[0028] The method for preparing an organic electrolyte comprises the following steps:
[0029] In a glove box filled with Ar (the content of moisture and oxygen is less than 0.01ppm), 1mL of EC+DMC ester-based mixed solvent was added to each of the three electrolyte bottles, 1mmol of KFSI was added to one electrolyte bottle, and the mixture was mixed to obtain 1M KFSI / EC+DMC potassium ion battery electrolyte (LIAE); 3mmol of KFSI was added to another electrolyte bottle, and the mixture was mixed to obtain 3M KFSI / EC+DMC potassium ion battery electrolyte (MIAE); 5mmol of KFSI was added to the last electrolyte bottle, and the mixture was mixed to obtain 5M KFSI / EC+DMC potassium ion battery electrolyte (HIAE).
[0030] Figure 1 The infrared spectrum of the electrolyte after adjusting the ion association characteristics and the 1270cm -1 The energy value calculated from the peak shift; due to the interaction between potassium ions and the electron-rich oxygen atoms in the solvent molecules, when the proportion of potassium ions gradually increases, the interaction between the two is further enhanced, and the free solvent is converted into a solvated state.
[0031] Figure 2 To control the Raman spectra of the electrolyte and obtain the solvation structure ratio and solvent coordination number after fitting, in order to prove the differences in the ion association properties of these designed electrolytes; with the increase of potassium salt concentration, FSI - and K + The ionic binding between them is enhanced, forming an anion-rich solvated structure with significantly suppressed free solvent.
[0032] Figure 3 The solubility performance of ferrocene in the regulated electrolyte was tested; and the upper transparent solution selected in the solubility test was subjected to UV-visible spectroscopy, with the corresponding electrolyte as the background, proving that with the enhancement of ion association, the solubility problem was significantly suppressed.
[0033] Example 2
[0034] In a glove box filled with Ar (the contents of moisture and oxygen were both less than 0.01 ppm), 1 mL of PC+DMC was taken, 3 mmol of KFSI was added to the mixed ester-based solvent, and the mixture was mixed to obtain a 3M KFSI / PC+DMC potassium ion battery electrolyte.
[0035] Using 3M KFSI / PC+DMC potassium ion battery electrolyte, Fc negative electrode material, and potassium metal as the counter electrode, a potassium ion half-cell was assembled to study the potassium storage performance of the Fc negative electrode material in PC-based MIAE.
[0036] K||K battery was assembled using 3M KFSI / PC+DMC potassium ion battery electrolyte, and the chemical stability of the electrolyte to potassium metal was studied.
[0037] Example 3
[0038] In a glove box filled with Ar (the contents of moisture and oxygen were both less than 0.01 ppm), 1 mL of VC+DMC was taken, 3 mmol of KFSI was added to the mixed ester-based solvent, and the mixture was mixed to obtain a 3M KFSI / VC+DMC potassium ion battery electrolyte.
[0039] Using 3M KFSI / VC+DMC potassium ion battery electrolyte, Fc negative electrode material, and potassium metal as the counter electrode, a potassium ion half-cell was assembled to study the potassium storage performance of the Fc negative electrode material in PC-based MIAE.
[0040] K||K battery was assembled using 3M KFSI / VC+DMC potassium ion battery electrolyte, and the chemical stability of the electrolyte to potassium metal was studied.
[0041] The experimental results of potassium storage performance of potassium ion half-cells obtained in the above examples 1-3 are as follows:
[0042] Figure 4 It shows that Fc at a current density of 50 mA g -1 The reversible capacity of the Fc anode in LIAE shows a gradual decay trend; after 200 cycles, its discharge capacity is 161.8 mAh g -1 This may be due to the decomposition of free solvent on the electrode surface and the dissolution of a small amount of active substances. Fc has the best electrochemical performance in MIAE, with a capacity of up to 210.9 mAh g after 200 cycles. -1, which is related to the change of the solvation configuration of the electrolyte, reducing the proportion of free solvent and enhancing the strength of ion binding. However, due to the increase in electrolyte viscosity and solvation structure volume, the capacity of Fc in HIAE did not show a trend of further increase.
[0043] Figure 5 The Fc anode exhibits excellent rate performance at higher current densities, which is attributed to the faster electron transfer rate and excellent reaction kinetics. -1 The display is 209, 165, 140, 129 and 114 mAh g respectively. -1 When the current density is restored to 50 mA g -1 It can still provide 200mAh g -1 In contrast, at the same current density, the discharge specific capacities of the Fc anode under LIAE and HIAE conditions were 155, 126, 101, 57, 35 and 184, 149, 115, 70, 52 mAh g -1 In addition, in MIAE, Fc is at 200 mA g -1 After 250 cycles under the same conditions, the reversible capacity is as high as 171.9 mAh g -1 This is due to the regulation of the degree of ion binding, which makes Fc have excellent cycling stability even at high current density.
[0044] Figure 6 The effect of regulating the ion association strength on the reaction kinetics and ion transport properties of Fc negative electrode materials was demonstrated. The average D K + The value of is the largest, which is attributed to its anion-rich solvation structure and moderate ion association, thus proving that this potassium storage system has faster ion transport and reaction kinetics. However, the viscosity of HIAE increases, the ion migration rate slows down, and the average D K + The value is smaller than LIAE and MIAE.
[0045] Figure 7 The effects of changes in the solvent molecular structure on the potassium storage performance of Fc were discussed. 3M KFSI / PC+DMC (PC-based MIAE) and 3M KFSI / VC+DMC (VC-based MIAE) electrolytes were designed to study the differences in electrochemical performance of Fc in EC-type MIAE, aiming to explain in more depth the effects of the physicochemical properties of the electrolyte on the electrode structure stability and electrochemical potassium storage performance. -1The reversible capacity of Fc in VC-based MIAE electrolyte shows a rapid decay trend with the cycling process. This is because the structure of VC is unstable and it is easy to form oligomers, which seriously hinders the transport of potassium ions. Due to the addition of side chains in the molecular structure, the capacity of the Fc negative electrode in the first 50 cycles of PC-based MIAE also decays, accompanied by fluctuations in coulombic efficiency. In EC-based MIAE, Fc has higher discharge capacity and faster kinetic characteristics, which shows the dependence of electrode materials on electrolyte design.
[0046] Figure 8 The rate performance comparison of Fc in electrolyte solvent-derived electrolytes is demonstrated. The rate performance in EC-based MIAE is much better and the redox reaction kinetics is faster.
[0047] Fig. 9 The performance of EC-based and PC-based MIAE potassium||potassium symmetric batteries was demonstrated to further verify their compatibility with potassium. Among them, the potential difference of PC-based MIAE was 0.44V; after 500 hours, the battery showed asymmetric deposition / dissolution behavior, which may be due to the generation of a large amount of "dead potassium". In contrast, in EC-based MIAE, the average potential difference of the potassium||potassium symmetric battery was around 0.16V, and the potential difference did not change significantly after 800 hours of stable cycling. This is because the regulation of ion binding properties enhances the compatibility of the electrolyte with potassium. In the rate performance test, the potassium||potassium symmetric batteries of the two electrolytes also showed the same trend as long cycling.
Claims
1. Application of a medium ion association electrolyte and a ferrocene (Fc) negative electrode material in a potassium ion half-cell, characterized in that: The potassium ion half-cell includes an organic electrolyte, Fc, and potassium metal; the organic electrolyte is prepared through an ion association strategy to obtain a potassium bis(fluorosulfonyl)imide (KFSI)-based electrolyte with different degrees of ion association; the negative electrode material is a commercial ferrocene material that has not been treated in any way.
2. The use of the medium ion association electrolyte and Fc negative electrode material in a potassium ion half-cell according to claim 1, characterized in that: Three solvents with different properties were used: mixed ester-based solvents of ethylene carbonate + dimethyl carbonate (EC + DMC) (volume ratio 1:1), propylene carbonate + dimethyl carbonate (PC + DMC) (volume ratio 1:1), and vinylene carbonate + dimethyl carbonate (VC + DMC) (volume ratio 1:1).
3. The use of the medium ion association electrolyte and Fc negative electrode material in a potassium ion half-cell according to claim 1, characterized in that: Preparation of electrolyte: In a glove box filled with argon (water and oxygen content <0.01ppm), add a certain amount of KFSI to the three solvents EC+DMC, PC+DMC, and VC+DMC, respectively, mix and stir evenly to obtain potassium ion battery electrolyte with a concentration of 1-5mol / L(M).
4. The use of the medium ion association electrolyte and Fc negative electrode material in a potassium ion half-cell according to claim 1, characterized in that: The mixing temperature was 30°C and the time was 12 h.